2011
DOI: 10.1177/8755123311418623
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Male Attitudes About Singing in Choir

Abstract: The purpose of this study was to investigate the factors that influence adolescent males to enroll in school choir as an elective class and to assess their attitudes about singing in general, self-concept of their own voices, and perception of others' view of adolescent males' participation in choir. Data were obtained from 101 adolescent males who were enrolled in choir at one of six participating schools, and were in Grade 7 or Grade 8. Data analysis showed that most participants enrolled in choir because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
9
0
3
Order By: Relevance
“…Hartley (1996) found that middle school students who enjoy playing their instruments tend to continue to participate in music performance programs. Kennedy (2002) and Lucas (2011), in studies of junior high school boys in choir, have found that love of singing is an important factor motivating boys’ enrollment and retention in choir. Clements (2002) examined whether gender affected factors motivating students’ retention in an ensemble.…”
Section: Attitude Toward Behaviormentioning
confidence: 99%
“…Hartley (1996) found that middle school students who enjoy playing their instruments tend to continue to participate in music performance programs. Kennedy (2002) and Lucas (2011), in studies of junior high school boys in choir, have found that love of singing is an important factor motivating boys’ enrollment and retention in choir. Clements (2002) examined whether gender affected factors motivating students’ retention in an ensemble.…”
Section: Attitude Toward Behaviormentioning
confidence: 99%
“…We thus find different studies on the common motivation for adolescent involvement with music from which we can extract the following: (a) the fulfilment of emotional needs (North, Hargreaves, & O’Neill, 2000; Roe, 1985); (b) distractions from boredom (Gantz, Gartenberg, Pearson, & Shiller, 1978; Lucas, 2011); and (c) the relief of tension and stress (Gantz et al, 1978).…”
Section: Singers’ Motivation In Relation To Musical Activitiesmentioning
confidence: 99%
“…curricular or pedagogical techniques in the ensemble classroom (Koops, 2009;Reynolds & Beitler, 2007;Riley, 2006) and the many ways puberty impacts vocal development and choral ensembles (Freer, 2010;Gackle, 1991Gackle, , 2006Kennedy, 2004;Killian, 1999;Lucas, 2011;Sweet, 2010Sweet, , 2015Zemek, 2010). Despite these many avenues of investigation around the teaching of young adolescents, the educational principles guiding the everyday choices made by music educators when working with young adolescents, particularly in non-ensemble settings, remain unclear.…”
mentioning
confidence: 99%
“…As a result, music education researchers have examined young adolescents’ motivation to participate in music as one line of middle school-focused inquiry (Bennetts, 2013; Campbell, 2009; Kennedy, 2002; Power, 2008; Saunders, 2010; Warnock, 2009). Other lines of inquiry in middle school music include the use of varied curricular or pedagogical techniques in the ensemble classroom (Koops, 2009; Reynolds & Beitler, 2007; Riley, 2006) and the many ways puberty impacts vocal development and choral ensembles (Freer, 2010; Gackle, 1991, 2006; Kennedy, 2004; Killian, 1999; Lucas, 2011; Sweet, 2010, 2015; Zemek, 2010). Despite these many avenues of investigation around the teaching of young adolescents, the educational principles guiding the everyday choices made by music educators when working with young adolescents, particularly in non-ensemble settings, remain unclear.…”
mentioning
confidence: 99%